Odpowiedzi

2009-11-20T18:46:15+01:00
X-2=x√3-2√3
x-2=-2x√3 / : -2
x=x√3
tego drugiego nie umiem ;/
Najlepsza Odpowiedź!
2009-11-20T19:47:19+01:00
(7-4√3)*(x+√3)=6
7x+7√3-4√3x-12=6
7x-4√3x=6+12-7√3
3√3x=11√3
x=11√3÷3√3
x=11√3/3√3=11/3

x-2=x√3-2√3
x-x√3=-2√3+2
x(1-√3)=-2√3+2
x=(-2√3+2)/(1-√3)=((-2√3*(1+√3)+2*(1+√3))/((1-√3)*(1+√3))=(-2√3-6+2+2√3)/1-3=-4/-2=2
2009-11-20T19:54:41+01:00
B)x-2=x√3-2√3
x - x√3 = 2 - 2√3
x(1-√3) = 2 (1 - √3) / : (1 - √3)
x = 2

a) (7-4√3)(x+√3)=6
7x + 7√3 - 4√3x - 12 = 6
7x - 4√3x = 18 - 7√3
x(7 - 4√3) = 18 - 7√3 / (7 - 4√3)
x = 18 - 7√3 / 7 - 4√3
x= (18 - 7√3) * (7 + 4√3) / 49 - 48
x = 126 + 72√3 - 49√3 - 84
x = 22 + 23√3